A review of organic inputs to inform soil health advice for African smallholder farmers: localization matters - Gudeta W. Sileshi; Zachary P. Stewart; Jonathan Odhong; Blessing Mhlanga; Tilahun Amede; Ermias Aynekulu; Christian Thierfelder; Paswel Marenya; Kyle M. Dittmer; Kamaluddin Tijjani Aliyu; Regis Chikowo; Mazvita Chiduwa; et al. (npj Sustainable Agriculture)
Abstract African smallholder farming systems are complex, diverse and locally adapted, but guidance is lacking on how farmers can make informed choices of the type of organic inputs to suit their farm conditions. In this review we aimed to provide a synthesis of actionable information on ex situ and in situ organic resources and decision support tools to facilitate evidence-based choices by smallholders in cereal production systems in sub-Saharan Africa.